2022
DOI: 10.3390/insects13030282
|View full text |Cite
|
Sign up to set email alerts
|

Short Neuropeptide F and Its Receptor Regulate Feeding Behavior in Pea Aphid (Acyrthosiphon pisum)

Abstract: Insect short neuropeptide F (sNPF), an ortholog of prolactin-releasing peptide of invertebrates, regulates diverse biological processes, including feeding, olfaction, locomotion, and sleep homeostasis in insects. However, its function is still unclear in an important model insect and agricultural pest, the pea aphid (Acyrthosiphon pisum). Here, we investigated short neuropeptide F (ApsNPF) and its receptor (ApsNPFR) in A. pisum. The sNPF gene contains three exons and two long introns. In addition, the genome c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…4A, B) based on RT-qPCR, which provided evidence that the sNPF signaling pathway is potentially related to the modulation of versatile physiological roles of M. separata. Both sNPF and sNPFR1 had significantly highest expression levels in the 1st instar larvae, which was consistent with sNPF and sNPFR in A. pisum (Peng et al, 2021) and R. padi (Amir et al, 2022). Tissue distribution of M. separata revealed that sNPF and sNPFR1 were highly expressed in the CNS, whereas sNPFR2 had higher transcript levels in the midgut and Malpighian tubules of larvae.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…4A, B) based on RT-qPCR, which provided evidence that the sNPF signaling pathway is potentially related to the modulation of versatile physiological roles of M. separata. Both sNPF and sNPFR1 had significantly highest expression levels in the 1st instar larvae, which was consistent with sNPF and sNPFR in A. pisum (Peng et al, 2021) and R. padi (Amir et al, 2022). Tissue distribution of M. separata revealed that sNPF and sNPFR1 were highly expressed in the CNS, whereas sNPFR2 had higher transcript levels in the midgut and Malpighian tubules of larvae.…”
Section: Discussionsupporting
confidence: 74%
“…Its cognate receptor sNPFR belongs to the rhodopsin superfamily of G protein-coupled receptors (GPCRs), which share a 7 α-helical transmembrane structure (Mertens et al, 2002). To date, sNPF and its receptor have been reported in many insects, such as Diptera (Nässel et al, 2008;Li et al, 2022), Orthoptera (Dillen et al, 2013(Dillen et al, , 2014, and Coleoptera (Marciniak et al, 2020;Liu et al, 2021a), Hemiptera (Peng et al, 2021;Amir et al, 2022), Hymenoptera (Lu & Pietrantonio, 2011;Bestea et al, 2022b), and Lepidoptera (Nagata et al, 2012;Ma et al, 2017;Cheng et al, 2021). These data suggest that sNPF family neuropeptide signals widely exist in insect species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that these insects are evolutionarily distant, it is likely that the shift in sNPF activity from feeding promotion to inhibition might have occurred repeatedly during the evolutionary process. In addition, a previous report demonstrated the role of sNPF in regulating insect feeding, such as in the hemiptera where it regulates the feeding behavior of pea aphid 21,22 . Therefore, it is reasonable to speculate that sNPF is potentially involved in nicotinic regulation of BPH feeding.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, a previous report demonstrated the role of sNPF in regulating insect feeding, such as in the hemiptera where it regulates the feeding behavior of pea aphid. 21,22 Therefore, it is reasonable to speculate that sNPF is potentially involved in nicotinic regulation of BPH feeding.…”
Section: Introductionmentioning
confidence: 99%